2019
DOI: 10.2217/rme-2018-0072
|View full text |Cite
|
Sign up to set email alerts
|

Poly-ε-Caprolactone and Polyvinyl Alcohol Electrospun Wound Dressings: Adhesion Properties and Wound Management of Skin Defects in Rabbits

Abstract: Aim: This study evaluates the effect of electrospun dressings in critical sized full-thickness skin defects in rabbits. Materials & methods: Electrospun poly-ε-caprolactone (PCL) and polyvinyl alcohol (PVA) nanofibers were tested in vitro and in vivo. Results: The PCL scaffold supported the proliferation of mesenchymal stem cells, fibroblasts and keratinocytes. The PVA scaffold showed significant swelling, high elongation capacity, limited protein adsorption and stimulation of cells. Nanofibrous dressings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Yet, a combination of PCL, gentamicin, and VitE in a clean, non-infected wound did not worsen the healing process. These results agree with our study of an acute skin defect treatment, where PCL nanofibers showed worse results than hydrophilic polyvinyl alcohol nanofibers [ 52 ]. A similar treatment in a porcine model of the chronic wound is currently being performed to confirm these results.…”
Section: Discussionsupporting
confidence: 92%
“…Yet, a combination of PCL, gentamicin, and VitE in a clean, non-infected wound did not worsen the healing process. These results agree with our study of an acute skin defect treatment, where PCL nanofibers showed worse results than hydrophilic polyvinyl alcohol nanofibers [ 52 ]. A similar treatment in a porcine model of the chronic wound is currently being performed to confirm these results.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the samples contained a minimum of spherical defects. The stereology of the scaffolds was in accordance with other findings [14,15]. The scanning electron microscope also showed a fine fibrin network formed on the surface of the plateletfunctionalized samples.…”
Section: Discussionsupporting
confidence: 88%
“…9 Besides, NPs promoted the wound recovery by boosting immunity, stimulating skin recovery, and killing bacteria. 10,11 For wound dressings, various materials have been used to protect the area around the wound, thereby promoting wound healing. 12 Different wound-healing methods exist in the literature, including allografts, autografts, and wound dressings, derived from biodegradable and biocompatible polymers, such as chitosan, collagen, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…For example, antigen-conjugated nanoparticles (NPs) have been proven to protect the wound from bacteria infection and to promote skin recovery and regeneration . Besides, NPs promoted the wound recovery by boosting immunity, stimulating skin recovery, and killing bacteria. , For wound dressings, various materials have been used to protect the area around the wound, thereby promoting wound healing. Different wound-healing methods exist in the literature, including allografts, autografts, and wound dressings, derived from biodegradable and biocompatible polymers, such as chitosan, collagen, and so on. This has led to the development of materials such as a traditional membrane, dressing material decorated with NPs and biological groups to improve the wound-healing efficiency. …”
Section: Introductionmentioning
confidence: 99%